Redefining risk: Human rights and elementary school factors predicting post-secondary access - Brown, Robert S.; Gallagher-Mackay, Kelly; Parekh, Gillian (Education Policy Analysis Archives, 2020)
While there is a widespread consensus that students’ pathways towards postsecondary education are influenced early in life, there is little research on the elementary school factors that shape them. Identifying educational ‘risk factors’ directs attention to barriers that may warrant scrutiny or action under human rights legislation. New findings from a unique, longitudinal data set collected and developed by the Toronto District School Board highlights key factors, established in elementary school, as to how many students do not enter into post-secondary studies in Ontario. The majority of students suspended at any time, students in self-contained special education programs, and/or students who missed more than 10% of classes in grade 4 do not go on to PSE. These organizational factors are more predictive of students’ acceptance to PSE than individualized measures of preschool readiness, academic achievement in grade 3, race or parental education. These structural ‘risks’ are strongly correlated with of race and disability. In light of research that identifies promising, evidence-based practices available to reduce these risks, breaking down these barriers should be a priority from the perspective of improving PSE access and overcoming what may well amount to systemic discrimination.